UMPSA receives courtesy visit from Jilin Institute of Chemical Technology and Phoenix Asia Academy of Technology - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 15 April 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently received a courtesy visit from a delegation from the Jilin Institute of Chemical Technology and Phoenix Asia Academy of Technology.